Enhancing Sustainable performance in SMEs: The Moderating Role of Green Technology Capability - Asif Z. Warsi; Farwa Shah; Dr. Huma Maqsood; Maryam Bibi (Indus Journal of Social Sciences, 2025)
This study investigates the drivers of green innovation and their impact on sustainable business performance in small and medium-sized enterprises (SMEs) in Pakistan, with a focus on the moderating role of green technology capability. Drawing upon the Natural Resource-Based View (NRBV), the research conceptualizes green absorptive capacity, sustainable human capital, and organizational support as key antecedents of green innovation while positing that green technology capability enhances these relationships. The study explores the influence of green innovation on the environmental, economic, and social dimensions of sustainable business performance. Using a quantitative research design, data were collected through a structured survey from 321 managers across various SME sectors in Pakistan. Structural Equation Modeling (SEM) was employed to test the hypothesized relationships. Contrary to expectations, the results reveal that green absorptive capacity, sustainable human capital, and organization support do not significantly predict green innovation, and green technology capability does not moderate these relationships. These findings suggest that internal capabilities, while theoretically relevant, may not translate into innovative environmental practices in resource-constrained SME environments without strategic alignment and operational integration. However, green innovation was found to have a significant and positive impact on all three dimensions of sustainable performance, environmental, economic, and social, affirming its role as a critical mechanism for achieving sustainability. The study offers important theoretical contributions by challenging the generalizability of conventional green innovation models in developing economies and emphasizing the need to examine contextual and institutional dynamics. Practically, it highlights the necessity for SME leaders to go beyond capability development and focus on implementation processes, technology integration, and innovation culture to realize sustainability goals.